Angelica Polysaccharide Antagonizes 5-FU-Induced Oxidative Stress Injury to Reduce Apoptosis in the Liver Through Nrf2 Pathway - Zeng, Di; Wang, Yaping; Chen, Yi; Li, Danyang; Li, Guoli; Xiao, Hanxianzhi; Hou, Jiyin; Wang, Ziling; Hu, Ling; Wang, Lu; Li, Jing (Frontiers in Oncology, 2021)
Oxidative stress induced by chemotherapeutic agents causes hepatotoxicity. 5-Fluorouracil (5-FU) has been found to have a variety of side effects, but its toxic effect on the liver and the mechanism are still unclear. Angelica polysaccharide (ASP), the main active ingredient of Dang Gui, has antioxidative stress effects. In this study, we investigated the antagonistic effects of ASP on 5-FU-induced injury in the mouse liver and human normal liver cell line MIHA and the possible mechanism. Our results show that ASP inhibited 5-FU-induced the decrease in Bcl-2 protein and the increase in Bax protein. ASP alleviated 5-FU-induced the increase in alanine aminotransferase (ALT), triglyceride (TG), and aspartate aminotransferase (AST) content; hepatic steatosis; and liver fibrosis. ASP restored 5-FU-induced swelling of mitochondria and the endoplasmic reticulum. 5-FU promoted the expression of Keap1 and increased the binding to NF-E2-related factor 2 (Nrf2) to reduce the nuclear translocation of Nrf2, thereby weakening the transcriptional activity of Nrf2 to inhibit the expression of HO-1; reducing the activity of GSH, SOD, and CAT to increase ROS content; and aggravating DNA damage (indicated by the increase in 8-OHdG). However, ASP reversed these reactions. In conclusion, ASP attenuated the 5-FU-induced Nrf2 pathway barrier to reduce oxidative stress injury and thereby inhibit the disorder of lipid anabolism and apoptosis. The study provides a new protectant for reducing the hepatic toxicity caused by 5-FU and a novel target for treating the liver injury.